POTRET JIWA KEWIRAUSAHAAN PENGUSAHA KERAJINAN UKIR JEPARA - Indrahti, Sri (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT The entrepreneurship of the success entrepreneur is always associated with capability, courage, dependability, and creativity. It’s belonged to the entrepreneur of carve industry in Jepara in 1990-2000 be in conformity with entry of exporter and international market. The things can be supported it, among other things: their capability to adapted with what people want and the solution is make an innovation (creativity), their honestly to do what the Islam says that work is a part of worship, and their orientation to gain. Keywords : entrepreneurship, the entrepreneur of carve industry in Jepara, honestly, innovation, gain.